Association of Genetic Variants of Dopamine and Serotonin In Schizophrenia - Zakharyan, Roksana; Ghazaryan, Hovsep; Kocourkova, Lenka; Chavushyan, Andranik; Mkrtchyan, Artur; Zizkova, Veronika; Arakelyan, Arsen; Petrek, Martin (Archives of medical research, 2020)
BACKGROUND: Several studies indicated that antipsychotic treatment response and side effect manifestation can be different due to inter-individual variability in genetic variations. AIM OF THE STUDY: Here we perform a case-control study to explore a potential association between schizophrenia and variants within the antipsychotic drug molecular targets (DRD1, DRD2, DRD3, HTR2A, HTR6) and metabolizing enzymes (CYP2D6, COMT) genes in Armenian population including also analysis of their possible relationship with disease clinical symptoms. METHODS: A total of 18 SNPs was studied in patients with schizophrenia (n = 78) and healthy control subjects (n = 77) using MassARRAY genotyping. RESULTS: We found that two studied genetic variants, namely DRD2 rs4436578*C and HTR2A rs6314*A are underrepresented in the group of patients compared to healthy subjects. After the correction for multiple testing, the rs4436578*C variant remained significant while the rs6314*A reported borderline significance. No significant differences in minor allele frequencies for other studied variants were identified. Also, a relationship between the genotypes and age of onset as well as disease duration has been detected. CONCLUSIONS: The DRD2 rs4436578*C genetic variant might have protective role against schizophrenia, at least in Armenians.
Keywords: schizofrenie; dospělí; studie případů a kontrol; katechol-O-methyltransferasa; Humans; Genetic Predisposition to Disease; genetická predispozice k nemoci; lidé středního věku; Gene Frequency; Middle Aged; Young Adult; Genotype; Receptors, Serotonin; Genetic Association Studies; Cytochrome P-450 CYP2D6; mladý dospělý; serotonin; metabolické sítě a dráhy; mužské pohlaví; receptory serotoninové; antipsychotika; Receptors, Dopamine; Adult; Serotonin; receptory dopaminové; frekvence genu; Metabolic Networks and Pathways; ženské pohlaví; Antipsychotic Agents; jednonukleotidový polymorfismus; genotyp; lidé; Case-Control Studies; Polymorphism, Single Nucleotide; Dopamine; Catechol O-Methyltransferase; Schizophrenia; Aged; cytochrom P-450 CYP2D6; senioři; Male; genetické asociační studie; dopamin; Female